Understanding exchange rate pass-through in Vietnam - Nga Nguyen Hong; Vo Thi Kim Loan; Pham Hoang An; Cuong Tran Quoc Khanh (Cogent Economics & Finance, 2022)
Price stability is the ultimate objective of the State Bank of Vietnam (SBV). In addition, in a small export-led economy, such as Vietnam, the study of exchange rate volatility is crucial for the country's economy due to its impact on inflation via exchange rate pass-through (ERPT). This study investigated ERPT in Vietnam by employing both autoregressive distributed lag (ARDL) and nonlinear-ARDL (NARDL) approaches with data spanning from January 2009 to May 2020. Our main findings suggest that the exchange rate and money supply are the two most important factors influencing the consumer price index (CPI) and explain the change in the CPI structure using the threshold model. In addition, the transition to a central-rate mechanism successfully lowered the inflation rate in Vietnam. Furthermore, the NARDL model displays short- and long-run exchange rate asymmetries. Based on this evidence, several policy implications are provided to support price-level stability.
Keywords: 330; asymmetric; ERPT; exchange rate regime; inflation; nonlinear-ARDL; threshold model; Vietnam